Quality of work-life in employees experiencing a job-skill mismatch - Arjuni, Rifka Fadhiilah; Priyatama, Aditya Nanda; Satwika, Pratista Arya (Faculty of Psychology and Health - Universitas Islam Negeri Walisongo Semarang, 2019)
Abstract: Quality of Work-life (QWL) in an employee is an important aspect to which a company needs to pay much attention, moreover if the employee experiences a job-skill mismatch. This study aimed to test the effect of job involvement and perceived happiness simultaneously and partially on the quality of work-life in an employee who experiences a job-skill mismatch. The instruments used for collecting data were the QWL scale, job involvement scale, and perceived happiness scale. The subjects of this study were 64 employees. The method of data analysis was the multiple regression analysis. The result of this study showed that job involvement and perceived happiness simultaneously affected QWL (r=0,763; p=0,000). Partially job involvement also had an effect on QWL (r=0.64; p=0,000) and perceived happiness on QWL (r=0,261; p=0,039). Simultaneously, the contribution of job involvement and perceived happiness to the QWL of the employees with a job-skill mismatch was 56.9%. It means that the higher the rate of job involvement and perceived happiness, the higher the quality of work-life an employee with a job-skill mismatch has, and vice versa.